The Effect of Coating on Leakage Current Characteristic of Coast Field Aged Ceramic Insulator - Dini Fauziah; Heldi Alfiadi; Rachmawati Rachmawati; Suwarno Suwarno (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
Ceramic insulator is widely used in Indonesian electrical power distribution system. Based on previous research, it is obtained that silicone rubber coating can improve the performance of ceramic insulator due to better hydrophobicity. This paper presents performance of ceramic insulator with and without silicone rubber coating in a coastal area of Pangandaran. 6 silicone rubber coated and 6 uncoated of 20 kV distribution insulators have been installed in the field to get natural aging process for 5 years and 4 months. Along the aging process, their surface properties have been checked periodically. Monitored parameters are magnitude of leakage current, THD, hydrophobicity, and surface temperature of insulator. The result has shown that after 5 years and 4 months aging in coastal area without maintenance, silicone rubber coated ceramic insulator has better performance.